Toleransi dalam Agama Hindu; Aplikasi Ajaran dan Praktiknya di Pura Jala Siddhi Amertha Sidoarjo - Achmad Zainul Arifin (Satya Widya: Jurnal Studi Agama, 2019)
In this article, it explains the tolerance that exists in the teachings of Hinduism, in terms of the concept of teachings, texts or memorabilia, and practices and forms of application. Then, related to the concept of teaching tolerance is very much in Hinduism. But, it will be explained a little which includes Tri Hita Karana which defines three balance relations. Then, there is Panca Sradha which means five beliefs in Hinduism. Then, Tat Twam Asih which means a teaching about morality in Hinduism. Then, there is Tri Kaya Parisudha which defines three behaviors that must be sanctified, and others. One of the most well-known questions and guidelines in the life of the nation and state is Bhinneka Tunggal Ika tan hana dharma mangrwa, which if concluded we (all religious people) have many ways to achieve unity. This study uses a qualitative method by conducting interviews and direct observation of Hindu religious figures in East Java, besides that the author also conducts literature studies on various Hindu religious references. This study found that there were a variety of activities carried out by Hindus in the Amertha Juanda Pura Jala siddhi containing tolerance. Usually they do Social Services, Indonesia Celebrates the Difference which is attended by all religious people, again Semalam Nusantara Sidoarjo is an activity that is attended by several different ethnic groups.